PENGARUH GREEN ACCOUNTING DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS (STUDI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI INDEX SAHAM SYARIAH INDONESIA TAHUN 2018-2022 - Rina Oktalia; Usdeldi; Ferri Saputra Tanjung (EKSYA : Jurnal Ekonomi Syariah, 2023)
Profitability is important for companies or investors because high profitability will provide a positive signal for companies and investors to invest their capital. This study aims to analyze the effect of green accounting and company size on profitability (a study of mining companies listed on the Indonesian Sharia Stock Index for 2018-2022). This study uses a type of quantitative research. The data used is secondary data with the panel data regression analysis method with the help of the e-view 12 program. The sample in this study consisted of 9 companies for 5 years which were obtained through the website www.idx.co.id. The results of this study indicate that green accounting has an effect on return on assets. Company size has a significant effect on return on assets. Meanwhile, green accounting and company size jointly affect the variable return on assets. To improve overall company performance management through company profitability management while still implementing green accounting and maintaining company size.